2015
DOI: 10.1088/1367-2630/17/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration-assisted entanglement harvesting and rangefinding

Abstract: We study entanglement harvested from a quantum field through local interaction with Unruh-DeWitt detectors undergoing linear acceleration. The interactions allow entanglement to be swapped locally from the field to the detectors. We find an enhancement in the entanglement harvesting by two detectors with anti-parallel acceleration over those with inertial motion. This enhancement is characterized by the presence of entanglement between two detectors that would otherwise maintain a separable state in the absenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
242
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(256 citation statements)
references
References 46 publications
9
242
5
Order By: Relevance
“…When one uses a partially transmitting mirror ( q < W cos 1) to sever the correlations across the horizon, local squeezing is inevitably produced according to equation (33). Furthermore, there may be other ways to sever the correlations across the horizon, for example by using two uniformly accelerated Unruh-DeWitt detectors in left and right Rindler wedges [40,41].…”
Section: Squeezing From Accelerated Mirrorsmentioning
confidence: 99%
“…When one uses a partially transmitting mirror ( q < W cos 1) to sever the correlations across the horizon, local squeezing is inevitably produced according to equation (33). Furthermore, there may be other ways to sever the correlations across the horizon, for example by using two uniformly accelerated Unruh-DeWitt detectors in left and right Rindler wedges [40,41].…”
Section: Squeezing From Accelerated Mirrorsmentioning
confidence: 99%
“…The vacuum state of a long-range field is unentangled with respect to its extended non-local modes but can be entangled with respect to local modes [1] corresponding to localized detectors. Extracting this naturally endowed resource from a quantum field vacuum via localized detectors, such as atomic probes, is called vacuum entanglement harvesting [2][3][4][5][6]. The process can be understood in the following terms: an actuator turns the interaction between these two detectors and the field on and off, resulting in two initially unentangled detectors evolving into an entangled pair, after ignoring, or tracing out, the field itself.…”
Section: Introductionmentioning
confidence: 99%
“…Further work showed that this entanglement can, in principle, be used to violate Bell inequalities [3]. The amount of entanglement depends on properties of the field, of the background spacetime [4,5] and of the atom trajectories [6].…”
Section: Introductionmentioning
confidence: 99%